RESPONSE OF SALT STRESSED ROSEMARY PLANTS TO ANTISTRESS AGENTS - Hanan Ali; Mona Attia (Scientific Journal of Flowers and Ornamental Plants, 2015)
A pot experiment was carried out during two successive seasons (2014 and 2015) at Salinity and Alkalinity Soil Research Laboratory in Alexandria. The goal of this work was to study the response of rosemary (Rosmarinus officinalis L.) plants irrigated with saline water at 0, 2000 and 4000 ppm NaCl  to the application of antistress agents (salicylic acid “SA”  at 0 and 0.2 mM and diatomaceous earth “DDM” at 0 and 6 g/10 kg soil). The effect of these antistress agents on the vegetative growth, volatile oil percentage and its chemical composition were recorded. In general results indicated that irrigation  with saline water and antistress agents ( DDM and SA each of them solely) had a significant effect on vegetative growth expressed as plant height, number of branches/plant, herb fresh and  air dry weights and volatile oil percentage as compared to control  in most treatments  in  both cuts of the two seasons. Moreover the plants receiveddiatomaceous earth (DDM) at 6 g/10 kg soil combined with irrigation with non saline water (tap water) recorded the highest values of vegetative growth and volatile oil percentage in both seasons at the two cuts. Also the highest camphor content was achieved with this treatment. Proline content was decreased with increasing the rate of diatomaceous earth followed by salicylic acid, this refers to the response of rosemary plants grown under salt stress to the application of antistress agents ( DDM and SA).